S-Methyl-L-Ergothioneine to L-Ergothioneine Ratio in Urine Is a Marker of Cystine Lithiasis in a Cystinuria Mouse Model - Miguel López de Heredia; Lourdes Muñoz; Ciriaco Carru; Salvatore Sotgia; Angelo Zinellu; Carmen Serra; Amadeu Llebaria; Yukio Kato; Virginia Nunes (MDPI AG, 2021)
Cystinuria, a rare inherited aminoaciduria condition, is characterized by the hyperexcretion of cystine, ornithine, lysine, and arginine. Its main clinical manifestation is cystine stone formation in the urinary tract, being responsible for 1-2% total and 6-8% pediatric lithiasis. Cystinuria patients suffer from recurrent lithiasic episodes that might end in surgical interventions, progressive renal functional deterioration, and kidney loss. Cystinuria is monitored for the presence of urinary cystine stones by crystalluria, imaging techniques or urinary cystine capacity; all with limited predicting capabilities. We analyzed blood and urine levels of the natural antioxidant L-ergothioneine in a Type B cystinuria mouse model, and urine levels of its metabolic product S-methyl-L-ergothioneine, in both male and female mice at two different ages and with different lithiasic phenotype. Urinary levels of S-methyl-L-ergothioneine showed differences related to age, gender and lithiasic phenotype. Once normalized by L-ergothioneine to account for interindividual differences, the S-methyl-L-ergothioneine to L-ergothioneine urinary ratio discriminated between cystine lithiasic phenotypes. Urine S-methyl-L-ergothioneine to L-ergothioneine ratio could be easily determined in urine and, as being capable of discriminating between cystine lithiasis phenotypes, it could be used as a lithiasis biomarker in cystinuria patient management.